2015
DOI: 10.1371/journal.pone.0143777
|View full text |Cite
|
Sign up to set email alerts
|

Rap1A Regulates Osteoblastic Differentiation via the ERK and p38 Mediated Signaling

Abstract: Rap1A is a member of small G proteins belonging to the Ras family. Recently, an integration of human genome-wide association studies (GWAS) and gene expression profiling study revealed that single-nucleotide polymorphisms (SNPs) within human Rap1A were strongly associated with narrow neck width in women. However, the regulatory role of Rap1A in osteoblasts remains to be elucidated. Here we report that Rap1A is a key regulator in osteoblast differentiation. Rap1A expression and activity were gradually enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 26 publications
(26 reference statements)
1
32
0
Order By: Relevance
“…These results are in agreement with those of previous reports [4] . During osteoblastic differentiation, Rap1 expression increases, which in turn promotes differentiation [4] .…”
Section: Activated Rap1a Induces Osteoblastic Differentiation In Preosupporting
confidence: 94%
See 2 more Smart Citations
“…These results are in agreement with those of previous reports [4] . During osteoblastic differentiation, Rap1 expression increases, which in turn promotes differentiation [4] .…”
Section: Activated Rap1a Induces Osteoblastic Differentiation In Preosupporting
confidence: 94%
“…During osteoblastic differentiation, Rap1 expression increases, which in turn promotes differentiation [4] . Although the mechanism for osteogenic differentiation remains unknown, Rap1 and PI3K/Akt signaling have been suggested to play important roles in the process [5] .…”
Section: Activated Rap1a Induces Osteoblastic Differentiation In Preomentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA oligonucleotides were designed to generate shRNAs against the open reading frame of mRNA 5'‐ GCTCAGT CTACGTTTAATGAT‐3' (Rap1A shRNA1) and 5'‐ CCGAGCAATTTACAGCAATGA ‐3' (Rap1A shRNA2) to knockdown the expression of Rap1A. PLKO.1/Rap1A shRNA was generated according to the previously reported method …”
Section: Methodsmentioning
confidence: 99%
“…Ultimately, when differentially expressed genes were assigned to pathways using the KEGG mapper, we found three NO-driven pathways, namely the Rap1 and PI3K-Akt signaling pathways, and focal adhesion, which links different pathways. Previous studies have reported the connection between NO and these signaling pathways in osteoblastic activity [49][50][51][52]. Thus, we suggest that the NO signaling molecule can drive genetic and molecular pathways with implicated roles in ESC-osteogenic differentiation.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 53%